PENGEMBANGAN SISTEM REKOMENDASI BERBASIS FILTERING COLLABORATIVE UNTUK E-COMMERCE DI PT. ARAH ENVIROMENTAL INDONESIA - Iwan Setiawan; Dede Handayani (Journal of Research and Publication Innovation, 2026)
The rapid development of information technology has significantly advanced the e-commerce sector, enabling users to purchase products easily without time or location limits. However, the vast number of available products often makes it difficult for users to choose the right ones. This study aims to develop a Filtering Collaborative -based recommendation system to help users find relevant products at PT. Arah Environmental Indonesia. The system considers three main criteria: product rating, sales volume, and customer clicks or views on a single product sample. The results show that the system can provide accurate and relevant recommendations, improving user shopping experiences and supporting the company’s marketing strategy.